Exploring the Factors that Facilitate Gender Disparity in Access to Fertile Farmlands in Nadowli-Kaleo District (International Journal of Scientific Research in Science and Technology, 2024)
The paper explores the factors contributing to gender disparity in access to fertile farmlands in the Nadowli-Kaleo district. It highlights the significant imbalance in land ownership between men and women, influenced by cultural norms, inheritance practices, and patriarchal systems. The study emphasizes the need for interventions to promote gender equity in land ownership and empower women economically. The research employed a case study design to investigate the specific phenomenon of gender disparities in land access in the Nadowli-Kaleo district. This approach allowed for an in-depth exploration of sociocultural, economic, and environmental factors contributing to the gender gap in land ownership. Purposive selection was used to choose 198 participants for the study. The study focused on individuals residing in the Nadowli-Kaleo district, particularly those involved in agriculture and land ownership. The participants ranged from 24 to 65 years old, providing diverse perspectives on the issue of gender disparities in access to farmland. Face-to-face interviews with the assistance of interview guides were utilized to collect data from the participants. The data collected were transcribed, organized, and presented with relevant quotations to support the findings. The study revealed a significant gender disparity in land ownership, with men predominantly owning larger tracts of farmland compared to women who typically owned 1-3 acres or none at all. Factors such as gender, kinship, marital status, and cultural customs were identified as influencing access to land in the district. Based on the findings, recommendations were made.